CHARACTERIZATION AND PHARMACOLOGICAL EVALUATION OF Β-LACTONE DERIVATIVE WITH NOVEL FUNCTIONAL GROUPS FROM MACROTYLOMA UNIFLORUM - Vasundhara Saxena, Sushil Giri, Goldee Yadav, Anushka Verma, Sayantan Datta, Sulakshana Pal Singh (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Macrotyloma uniflorum (horse gram) is a nutritionally rich yet underexplored medicinal plant traditionally used in Ayurvedic and Unani medicine. Despite its widespread applications, limited studies have investigated its bioactive phytoconstituents. This study aims to isolate, characterize, and evaluate the bioactivity of Compound from Macrotyloma uniflorum. The ethanolic extract of Macrotyloma uniflorum was subjected to column chromatography, leading to the isolation of the Compound. The structure of the Compound was elucidated using infrared (IR) spectroscopy, nuclear magnetic resonance (NMR), and mass spectrometry (MS). Its antimicrobial and antioxidant activities were assessed using the agar well diffusion method and DPPH radical scavenging assay, respectively. Spectral analysis confirmed that Compound is a β-lactone derivative with a fused cyclohexene moiety. The compound exhibited moderate antibacterial activity against Staphylococcus aureus and Escherichia coli, with inhibition zones of 14 mm and 12 mm, respectively. Additionally, the DPPH scavenging assay revealed 72.3% antioxidant activity at 100 µg/mL, indicating strong free radical neutralization potential. This study identifies Compound as a bioactive lactone derivative, demonstrating antimicrobial and antioxidant properties. Given its pharmacological potential, further research is recommended for in-vivo validation and therapeutic applications. This study establishes a foundation for harnessing Macrotyloma uniflorum as a source of novel natural products in pharmaceutical research.